Erythrocyte Profile of Three Spot Gourami (Trichogaster trichopterus PALL) Infected by Digenetic Trematode Parasite (Clinostomum sp.) - Iqbal, Muhammad; Riauwaty, Morina; Syawal, Henni (Jurnal Akuakultur SEBATIN, 2026)
The three spot gourami (Trichogaster trichopterus) is a highly sought-after commodity by the community, often processed into salted fish or consumed fresh.. Clinostomum sp. infection, also known as "yellow grub", is a disease in fish caused by the digenea trematode parasite. This parasite is zoonotic, which means it can be transmitted to humans, especially through consumption of raw or undercooked freshwater fish. In humans, this infection can cause laryngo-pharyngitis (inflammation of the throat) and in severe cases, can cause death due to lack of oxygen (asphyxia). The study was conducted from September 2023 to January 2025, at the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine Sciences, Universitas Riau. The purpose of the study was to determine the erythrocyte profile of marsh gourami infected with the digenea trematode parasite (Clinostomum sp.). The method used in this study was the purposive sampling survey method. Sampling was carried out at the FPK UNRI Reservoir with 3 location points and the total number of sample fish was 180. The results showed that fish infected with Clinostomum sp. had an erythrocyte count of 0.84–1.07 × 10⁶ cells/mm³, a hemoglobin level of 4.29–4.54 g/dL and a hematocrit value of 21.7–27.3%. The range of water quality in the FPK reservoir during the study was a temperature of 26.0-31.2oC, pH ranging from 4.2to 6.1 and DO values ranging from 4.3-6.8 mg/L. Based on the data obtained, it can be concluded that Clinostomum sp. infection can affect fish health